Playing violent videogames does not influence traffic aggression in young adults. - Dorantes Argandar, Gabriel (Universidad Autónoma de Tamaulipas, 2017)
The use of violent videogames is commonly associated to aggressive behavior, especially amongst youngsters. Are these variables related? The use of videogames is understood as playing on computerized systems for purpose of entertainment, and traffic aggression is defined as any behavior that has the goal of reducing the well-being of one or more individuals in the context of driving a motor vehicle. This study had the purpose to establish the connection between these two variables, by means of a quantitative, cross-sectional and ex-post facto methodology and previously designed questionnaires. A collection of 217 participants that met this study’s requirements was conformed, most of which were young men with some university studies. A statistical relationship between use of violent videogames and aggressive behavior while driving could not be found.